Pengaruh Sistem Informasi Administrasi Kependudukan Terhadap Efektivitas Kerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wajo - Reza Annas Tasya Syam; Muh Hasbi Abbas; Asmanurhidayani Asmanurhidayani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research was conducted to determine the influence of the population administration information system on work effectiveness. Apart from that, the general aim of this research is to determine the magnitude of the influence of the population administration information system on the work effectiveness of employees at the Wajo Regency Population and Civil Registration Service office. This type of research uses a census type with a total of 26 respondents and uses a quantitative descriptive study. The data collection techniques used are observation, questionnaires and documentation. The research population is operators using the Population Administration Information System (SIAK) of the Population and Civil Registration Service Office of Wajo Regency. This research uses correlation coefficient analysis techniques and simple linear regression tests. The results of this research show that the population administration information system is in the very good category, employee work effectiveness is in the very good category, the Population Administration Information System has a positive effect on the work effectiveness of employees at the Wajo Regency Population and Civil Registration Service office.